Inhibition of Biofilm Formation of Foodborne Staphylococcus aureus by the Citrus Flavonoid Naringenin - Qing-Hui Wen (MDPI AG, 2021)
Taking into consideration the importance of biofilms in food deterioration and the potential risks of antiseptic compounds, antimicrobial agents that naturally occurring are a more acceptable choice for preventing biofilm formation and in attempts to improve antibacterial effects and efficacy. Citrus flavonoids possess a variety of biological activities, including antimicrobial properties. Therefore, the anti-biofilm formation properties of the citrus flavonoid naringenin on the Staphylococcus aureus ATCC 6538 (S. aureus) were investigated using subminimum inhibitory concentrations (sub-MICs) of 5~60 mg/L. The results were confirmed using laser and scanning electron microscopy techniques, which revealed that the thick coating of S. aureus biofilms became thinner and finally separated into individual colonies when exposed to naringenin. The decreased biofilm formation of S. aureus cells may be due to a decrease in cell surface hydrophobicity and exopolysaccharide production, which is involved in the adherence or maturation of biofilms. Moreover, transcriptional results show that there was a downregulation in the expression of biofilm-related genes and alternative sigma factor sigB induced by naringenin. This work provides insight into the anti-biofilm mechanism of naringenin in S. aureus and suggests the possibility of naringenin being used in the industrial food industry for the prevention of biofilm formation.